Principal’s Strategies in Improving Employee’s Performance (Study at SMA Negeri South Bengkulu) - Anitasari, Rozi; Lorita, Evi; Yusuarsono, Yusuarsono; Rikardo, Yanuar (Iapa Proceedings Conference, 2023)
This study aims to determine the Principal's Strategy in Improving Employee Performance (Study at SMA Negeri 1 Bengkulu Selatan). This research is qualitative research which is presented descriptively. There were 6 informants in this study consisting of: 2 key informants and 4 key informants. Methods of data collection through interviews, observation, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion, it is known that employee performance (a study at SMA Negeri 1 Bengkulu Selatan has been carried out). This can be seen from the indicators discussed earlier, namely: (1) Positive Encouragement: there is an award given by the school principal to TU employees and the teacher council who have achieved achievements assessed by the school principal, in the form of a charter. (2) Perform a Performance Audit: Every year the principal conducts an audit both in terms of finance and performance checks of employees, both the teacher council and TU staff to assess performance results. (3) Set Performance Standards and Goals: The principal assigns duties and responsibilities to the teacher council and TU staff in accordance with their respective duties in carrying out their duties. (4) Give Feedback: To Employees Regarding Their Performance The principal can see from the absence of teachers and TU staff to check the attendance of early or late employees whether or not the tasks assigned are carried out. (5) Give Employees Compliments or Other Rewards Related to Performance. The existence of praise given or carried out by the principal to the staff of the teacher council, TU and students who excel by giving some kind of reward can be in the form of money that has been budgeted by the school committee.